Advances in Computational Science and Computing - Xiong, Ning.; Xiao, Zheng; Tong, Zhao.; Du, Jiayi; Wang, Lipo.; Li, Maozhen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book includes papers on the recent advances in state-of-the-art computational science and computing presented at the 2018 International Symposium on Computational Science and Computing (ISCSC 2018), held in Huangshan, China, from 28 to 29 July 2018. All the papers were rigorously peer-reviewed by experts in the area. It is a valuable resource for researchers, professors, graduate students, as well as R & D staff in the industry with a general interest in computational science and computing.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence